Experiences of End-of-Life Decision-Making in Equine Veterinary and Charity Teams - Amelia Cameron; Megan Geldard; Tim Mair; Gary England; John Burford; Sarah Freeman; Kristian Pollock; Eleanor Wilson (Animals)
Veterinary and charity teams are frequently involved in equine end-of-life decisions. These can cause ethical dilemmas and emotional burdens and complicate communication with owners. Semi-structured focus groups explored experiences of making decisions about end-of-life care and euthanasia at three UK equine veterinary practices and one charity. There were 26 participants in a mix of roles. Inductive coding was conducted during thematic analysis. Major themes generated were ‘Equine Welfare’, ‘Relationships’, ‘Decision-Making’, and ‘Emotional Toll and Coping Strategies’. Communication, finances, and chronic vs. acute cases were key issues featured within multiple themes. The individual horse’s welfare was the participants’ priority during decision-making. However, there were barriers to coming to a decision about treatment or euthanasia, and conflict caused by these barriers could detrimentally affect participants’ mental health. Preferred style of decision-making varied depending on the situation. Examples given included shared decision-making, participants steering the decision, and attempts by participants or owners to shift decisional responsibility onto the other party. Some owners sought additional input into decisions from veterinary nurses and receptionists. Participants found aspects of their roles emotionally challenging. This could be mitigated by supportive relationships and communication with colleagues. Involving veterinary team members in varying roles in end-of-life care planning and euthanasia decision-making with owners contributes a range of skills and expertise and helps to share the burden of responsibility.